Interculturalidad y su desarrollo cognitivo de los niños de educación inicial de la Unidad Educativa Juan e Verdesoto - Pérez Zamora, Natali Elena (2019)
The present case study is evidenced in the Juan E Verdesoto educational unit of the city of Babahoyo, in the adaptation of children from different regions, countries that emigrate to our city and children with physical difficulties, or disorders that learn at different rates in their cognitive development guided by the teacher that dynamically, looking for strategies to include others and can share in the classroom, so that children are not discriminated against by their peers. It is important that the teacher is updated in the knowledge, trained or in turn investigated in the cases of children entering the classroom, for which the initial education curriculum of the ministry of education, in the field of coexistence indicates activities of Participate group games following the rules and assuming roles that allow you to maintain a harmonious environment with your peers and the field relations with the natural and cultural environment. Identify socio-cultural practices in your area showing curiosity about their traditions. This makes reference that the teacher must work creatively with the children to the integration of interculturality promoting respect for others. Surveys were carried out on teachers, parents and the campus director in which the importance of interculturality at the education level is demonstrated